Extra patient movement during mammographic imaging: an experimental study - Ma, W K (Br J Radiol, 2014)
OBJECTIVE: To determine if movement external to the patient occurring during mammography may be a source of image blur. METHODS: Four mammography machines with eight flexible and eight fixed paddles were evaluated. In the first stage, movement at the paddle was measured mechanically using two calibrated linear potentiometers. A deformable breast phantom was used to mimic a female breast. For each paddle, the movement in millimetres and change in compression force in Newton was recorded at 0.5- and 1-s intervals, respectively, for 40 s with the phantom in an initially compressed state under a load of 80 N. In the second stage, clinical audit on 28 females was conducted on one mammography machine with the 18 × 24- and 24 × 29-cm flexible paddles. RESULTS: Movement at the paddle followed an exponential decay with a settling period of approximately 40 s. The compression force readings for both fixed and flexible paddles decreased exponentially with time, while fixed paddles had a larger drop in compression force than did flexible paddles. There is a linear relationship between movement at the paddle and change in compression force. CONCLUSION: Movement measured at the paddle during an exposure can be represented by a second order system. The amount of extra patient movement during the actual exposure can be estimated using the linear relationship between movement at the paddle and the change in compression force. ADVANCES IN KNOWLEDGE: This research provides a possible explanation to mammography image blurring caused by extra patient movement and proposes a theoretical model to analyse the movement.